169k views
0 votes
(2/5 + 4/9 - 2/3) multiplied by 5/2 - 3/5

1 Answer

2 votes

Answer:

Explanation:

Least common denominator of 5 , 9 , 3 = 45


(2)/(5)+(4)/(9)-(2)/(3)=(2*9)/(5*9)+(4*5)/(9*5)-(2*15)/(3*15)\\\\=(18)/(45)+(20)/(45)-(30)/(45)\\\\= (18+20-30)/(45)\\\\= (8)/(45)\\\\

Least common denominator of 2, 5 = 10


(5)/(2)-(3)/(5)=(5*5)/(2*2)-(3*2)/(5*2)\\\\=(25)/(10)-(6)/(10)\\\\=(25-6)/(10)\\\\= (19)/(10)


((2)/(5)+(4)/(9)-(2)/(3))*((5)/(2)-(3)/(5))=(8)/(45)*(19)/(10)\\\\= (4*19)/(45*5)\\\\= (76)/(225)

User Benwixen
by
4.9k points